The Contents of Herbal and Dietary Supplements Implicated in Liver Injury in the United States Are Frequently Mislabeled. Issue 6 (3rd April 2019) - Navarro, Victor; Avula, Bharathi; Khan, Ikhlas; Verma, Manisha; Seeff, Leonard; Serrano, Jose; Stolz, Andrew; Fontana, Robert; Ahmad, Jawad
Abstract : The U.S. Drug Induced Liver Injury Network assayed the contents of herbal and dietary supplements collected from patients enrolled into its prospective study. The aim was to determine the accuracy of product labels, and to identify known hepatotoxins. Using high‐performance liquid chromatography coupled with mass spectrometry to assay 272 product, 51% were found to be mislabeled; that is, to have chemical contents that did not match the label. Appearance enhancement, sexual performance, and weight loss products were most commonly mislabeled. Whether the mislabeling contributed to liver injury is under study; however, the high mislabeling rate underscores the need for more stringent regulation of supplements. Abstract : Herbal and dietary supplements can cause liver injury. The precise cause for injury due to supplements is difficult to determine, as this studies shows that labels are largely unreliable.